Mouthguard use and attitudes regarding dental trauma among elite cross-country mountain biking and field hockey athletes - Monteiro Monnerat Tinoco, J.; Moura Sassone, L.; Harris Stevens, R.; Deluiz Martins, D.; Alves Grangeiro Neto, J.; Muniz Barretto Tinoco, E. (Dental Traumatology, 2020)
Background/Aims: Cross-country mountain biking and field hockey are two Olympic sports that pose a potential risk for dentofacial trauma. However, mouthguard use is not mandatory in either of these sports and knowledge about tooth rescue among athletes is often neglected. The aim of this cross-sectional epidemiological survey was to evaluate the prevalence of sports-related dentofacial injuries, mouthguard use and attitudes regarding tooth rescue among cross-country mountain biking and field hockey athletes participating at pre-Olympic competitions held in Rio de Janeiro, Brazil.